Minireview high-fructose diet and the ultrastructure of brain synapses - Marcello G. Marc (Élelmiszervizsgálati közlemények, 2020)
The brain is the hungriest organ. With this great energy demand, the brain’s function may depend on what it is being fed to a greater extent than previously appreciated. Consumption of fructose and glucose in sustained high quantities in industrially processed foods and beverages in the modern Western diet raises complex questions of metabolic, and neurological well-being. Here, we review the effects of sugar on hippocampus associated short term memory. The following work on rodent models, and human clinical trials expound the influence of increased fructose versus glucose, or starch intake on the synaptic organization of a brain region extensively involved in cognitive functions. Through the well supported structure-function relationship of dendritic synapse profiles, synaptic functionality effects of increased fructose versus glucose consumption on hippocampal synapse ultrastructure may be seen. Together with behavioral, and functional findings, ultrastructural data demonstrate potential changes in hippocampal associated cognitive processes directly related to either elevated fructose or glucose intake.